Vulnerability to assault injury: an emergency department perspective. Issue 10 (22nd September 2009) - Sivarajasingam, V; Morgan, P; Shepherd, J; Matthews, K
Abstract : Objective: To evaluate risk and protective factors for violence-related injuries from an emergency department (ED) perspective. Method: Three study groups were recruited: (1) patients attending a major ED who had suffered an assault (n = 148), (2) patients attending a major ED who had not suffered an assault (n = 151) and (3) non-patients from public places in Cardiff (n = 171). Participants completed one of two proforma questionnaires: questions related to sociodemographic factors including their alcohol consumption and, for those in the assault group, the circumstances of the assault injury. Results: The non-assault groups consumed more alcohol units per annum but fewer alcohol units per drinking session than the assault group. The assault group visited entertainment venues more frequently than the non-assault groups. The relationship between alcohol units consumed per drinking session and the risk of assault injury was non-linear. The risk of assault injury increased for both genders with alcohol consumption (up to 5 units for women and 11 units for men), but at a slower rate for women. The model predicted that, at zero alcohol consumption, the risk of assault injury in men and women was similar. Conclusions: In the context of the number of alcohol units consumed in a drinking session, the risk of sustaining injury in assault for men and women is different. The risk of injury in assault for men and women is the same when no alcohol is consumed. Alcohol consumption may lead to different risk-taking behaviour in men and women.